2013
DOI: 10.1136/bjsports-2013-092354
|View full text |Cite
|
Sign up to set email alerts
|

High ambulatory blood pressure in male professional football players

Abstract: Background No data exist on ambulatory blood pressure (ABP) in athletes. Objectives To identify ABP and examine recommended follow-up of high office blood pressure (OBP) in male professional football players and secondary study indicators of sympathetic activity. Methods Players with high OBP (cases) from a previous screening of 594 players (n=28) were matched for age and ethnicity with players with optimal OBP (controls). High ABP was defined as a mean of ≥135/85 mm Hg during daytime and ≥120/75 mm Hg during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
0
31
1
Order By: Relevance
“…In our sample of middle-aged endurance athletes, the proportion of athletes with masked hypertension was substantially higher (38%) than estimates from the general population (8-20%) [8], but comparable to male professional football players [20]. Importantly, the prevalence of masked hypertension depends on the definition.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In our sample of middle-aged endurance athletes, the proportion of athletes with masked hypertension was substantially higher (38%) than estimates from the general population (8-20%) [8], but comparable to male professional football players [20]. Importantly, the prevalence of masked hypertension depends on the definition.…”
Section: Discussioncontrasting
confidence: 48%
“…Although exercise training in general may prevent hypertension by positively affecting endothelial function and arterial stiffness [22,23], repetitive episodes of high-intensity strength or endurance exercise may contribute to a rise in BP, possibly by an increased sympathetic activity [6,20]. However, our study was not intended to demonstrate a causal relationship between endurance sports practice and masked hypertension.…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence figures of hypertension in athletes varies greatly between studies, being 7% for male professional football (soccer) players59 and 19% for collegiate (US) football players 60. A recent systematic review61 showed a prevalence of hypertension in the range of 0 to 45% for different populations, possibly attributable to various quality of methodology used in available studies.…”
Section: Introductionmentioning
confidence: 99%
“…As several studies have demonstrated increased left ventricular mass and increased left atrium size in athletes,12 it is possible that high BP may be a contributing factor13 14 that may also link to the increased risk of atrial fibrillation in endurance athletes 15–17. Hence, there is increasing interest in BP in athletes 14 18 19. BP measurement during preparticipation screening of athletes should be performed according to ‘best clinical care’,20 as outlined in the European Society of Cardiology's guidelines, with hypertension defined as systolic BP (SBP) ≥140 mm Hg and/or diastolic BP (DBP) ≥90 mm Hg after repeated measurements 21.…”
Section: Introductionmentioning
confidence: 99%